Experimental type 2 diabetes induction reduces serum vaspin, but not serum omentin, in Wistar rats. Issue 1 (25th April 2017) - Castro, Cynthia Aparecida de; da Silva, Karina Ana; Buffo, Marina Molina; Pinto, Karina Nogueira Zambone; Duarte, Fernanda de Oliveira; Nonaka, Keico Okino; Aníbal, Fernanda de Freitas; Duarte, Ana Cláudia Garcia de Oliveira
Summary: Vaspin and omentin are adipose tissue adipokines that have often been related to obesity and its comorbidities. The aim of this study was to investigate the behaviour of serum omentin and vaspin in models of type 2 diabetes. To do this, Wistar rats ( 200 g) were randomly divided into two groups: a non‐diabetic group ( n = 6) and a diabetic group fed on a high‐fat diet ( n = 6) and a low dose of streptozotocin (Sigma ® ). All procedures were approved by the Brazilian Ethics Committee. Body weight (BW) and food intake were recorded daily. Tail blood glucose levels were assessed at the end of the diabetes induction period. The insulin tolerance test (ITT) was performed after the diabetes induction period (7 weeks). The serum and tissues (liver, pancreas, and retroperitoneal (RET), epididymal (EPI) and visceral (VIS) white adipose tissues) were immediately removed and weighed. Analyses of levels of insulin, omentin, vaspin, adiponectin and inflammatory cytokines IL‐6, IL‐8 (CXCL8), TNF‐α and C‐reactive protein (CRP) in serum were performed using the enzyme‐linked immunosorbent assay (ELISA). Our results showed that IL‐8 and CRP serum levels in the diabetic group were significantly higher than in the non‐diabetic group. Vaspin and adiponectin values were lower for the diabetic group than for the non‐diabetic group. Omentin, IL‐6 and TNF‐α values did not differ between the groups. Our results showed that both the metabolism of the adipose tissue and the secretion of adipokines may be affected in diabetic rats. Omentin showed no difference between the groups, although the vaspin values decreased in the diabetic group.